2022
DOI: 10.1055/s-0042-1757896
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Acoustic Rheometry to Measure Coagulation Kinetics in Hemophilia A and Healthy Plasma: A Novel Viscoelastic Method

Abstract: Compared with conventional coagulation tests and factor-specific assays, viscoelastic hemostatic assays (VHAs) can provide a more thorough evaluation of clot formation and lysis but have several limitations including clot deformation. In this proof-of-concept study, we test a noncontact technique, termed resonant acoustic rheometry (RAR), for measuring the kinetics of human plasma coagulation. Specifically, RAR utilizes a dual-mode ultrasound technique to induce and detect surface oscillation of blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Consequently, the most popular papers from each category are identified separately. Tables 3 and 4 respectively list the top 25 downloaded articles from STH in 2023 (from 2022 and 2023 inclusive), as eligible for either the “free access” ( Table 3 ) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 or “general category” ( Table 4 ) 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 awards.…”
Section: “Most Popular” Article Awardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the most popular papers from each category are identified separately. Tables 3 and 4 respectively list the top 25 downloaded articles from STH in 2023 (from 2022 and 2023 inclusive), as eligible for either the “free access” ( Table 3 ) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 or “general category” ( Table 4 ) 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 awards.…”
Section: “Most Popular” Article Awardsmentioning
confidence: 99%
“…The publisher of STH, Thieme, had in the past provided most material related to COVID-19 as free to download, and so COVID19-related material is less likely to be itemized in the “general category” list of most popular. 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 The 25 most popular non-free to download papers are listed in Table 4 . The first two papers listed are the official winners of the 2024 Most Popular in the general category.…”
Section: “Most Popular” Article Awardsmentioning
confidence: 99%
“…Resonant acoustic rheometry (RAR) is a newly developed ultrasound-based technique for non-contact, rapid characterization of viscoelastic soft materials 14 . In a recent study, we demonstrated the feasibility of RAR for quantification of coagulation characteristics of human hemophilia A plasma samples 15 . RAR utilizes a dual-mode ultrasound technique that has unique advantages for longitudinal characterization of temporally evolving soft materials in a non-contact fashion.…”
Section: Introductionmentioning
confidence: 99%
“…4 Basic coagulation assays do not provide information regarding the rate and strength of clot formation and lysis. 5 In addition, these tests may show discrepancies against the clinical phenotype and FVIII activity. 4 ROTEM can perform several different assays simultaneously: intrinsic activation, extrinsic activation, and functional fibrinogen assay and permits monitoring of results in real time, including clot formation and dissolution in whole blood.…”
mentioning
confidence: 99%